Can Schools Change Religious Attitudes? Evidence from German State Reforms of Compulsory Religious Education - Benjamin W. Arold; Ludger Woessmann; Larissa Zierow (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study whether compulsory religious education in schools affects students' religiosity as adults. We exploit the staggered termination of compulsory religious education across German states in models with state and cohort fixed effects. Using three different datasets, we find that abolishing compulsory religious education significantly reduced religiosity of affected students in adulthood. It also reduced the religious actions of personal prayer, church-going, and church membership. Beyond religious attitudes, the reform led to more equalized gender roles, fewer marriages and children, and higher labor-market participation and earnings. The reform did not affect ethical and political values or non-religious school outcomes.
Keywords: Z12; I28; H75; 330; religious education; religiosity; school reforms